2016
DOI: 10.11646/zootaxa.4171.3.11
|View full text |Cite
|
Sign up to set email alerts
|

New species and records of Microveliinae and Veliinae (Hemiptera: Heteroptera: Veliidae) from Colombia

Abstract: Euvelia orinoquia sp. nov. and E. meta sp. nov. from eastern Colombia are described, illustrated, and included in an updated identification key to the species of the genus. The former can be diagnosed by body length 2.30-2.50 mm, male fore femur without tufts of setae, longitudinal black stripe of female pronotum almost twice as wide as length of antennomere I, and female connexiva grayish black with silvery pruinosity on mesal portion, reddish on lateral portion. Euvelia meta sp. nov. can be diagnosed by fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
1
9
0
5
Order By: Relevance
“…The remaining six species represented in our samples are new for the Vale do Ribeira region. Microvelia venustatis is widely distributed in South America (Molano et al 2016) and was previously reported from localities on northeastern and central São Paulo state Cordeiro and Moreira 2015). The new record we provide lies in a gap between the nearest occurrences to the north (São Paulo state, Ubatuba, Serra do Mar State Park, ca 350 km; Cordeiro and Moreira 2015) and to the south (Santa Catarina state, Seara, Nova Teutônia, ca 530 km; Drake and Plaumann 1955).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The remaining six species represented in our samples are new for the Vale do Ribeira region. Microvelia venustatis is widely distributed in South America (Molano et al 2016) and was previously reported from localities on northeastern and central São Paulo state Cordeiro and Moreira 2015). The new record we provide lies in a gap between the nearest occurrences to the north (São Paulo state, Ubatuba, Serra do Mar State Park, ca 350 km; Cordeiro and Moreira 2015) and to the south (Santa Catarina state, Seara, Nova Teutônia, ca 530 km; Drake and Plaumann 1955).…”
Section: Discussionsupporting
confidence: 57%
“…Known distribution. Argentina, Brazil, Colombia, Paraguay, Peru (Molano et al 2016). Distribution in Brazil.…”
Section: Microvelia Venustatis Drake and Harris 1933mentioning
confidence: 99%
“…Comments. Euvelia meta was first described based on a female specimen from Meta Department, Colombia, without any further records (Molano et al, 2016). It is herein recorded for the first time from Amazonas and Vichada departments (Fig.…”
Section: Diagnosis Recognized By the Following Combination Of Characmentioning
confidence: 97%
“…Euvelia meta Molano, Moreira & Morales, 2016 Diagnosis. This species can be recognized by the body length (1.20 -1.50 mm) and patches of silvery setae on male abdominal mediotergites II and V-VII, and on laterotergites I and IV-VI (Fig.…”
Section: Diagnosis Recognized By the Following Combination Of Characmentioning
confidence: 99%
“…Los géneros más diversos en Colombia son Microvelia y Rhagovelia, debido a la ampliación de registros y a la descripción de nuevas especies. El primero contaba hasta 1992 con cinco especies y a la fecha presenta 20 especies; el segundo pasó de 21 especies en 1997 a 80 especies actualmente (Padilla-Gil y Damgaard, 2011; Padilla-Gil y Moreira, 2011; 2013; Padilla-Gil y Pacheco-Chaves, 2012; Morales-C y Castro-Vargas, 2013;Padilla-Gil, 2013d;2019a;Aristizábal-García et al, 2015;Floriano et al, 2016;2019;Molano et al, 2016;2017;2018a;Castro-Vargas et al, 2018;Martínez et al, 2019;Polhemus et al, 2019;Rodrigues y Álvarez, 2019).…”
Section: Tendencias Del Estudio De Los Gerromorfos En Colombiaunclassified